Nowe derywaty czasownikowe - Kudra, Barbara (Acta Universitatis Lodziensis. Folia Linguistica, 1995)
New verbal derivatives, previously not included in dictionaries, have appeared in modern Polish language. The above article analyses the word-formative mechanisms present in their formation (the kind of derivative and the type of derivation). In prefixal verbal derivatives of the type popolemizować, zagłosować, zdokumentować mainly the perfective properties of prefixes are brought out. In suffixal derivatives of the type premierować, rzecznikować, tabuizować the tendency to shorten linguistic expressions, still alive in the Polish language, appears; the shortened expressions are derived from multiword expressions, e.g. premierować – być premierem (to be the Prime Minister), etc. The prefixal-suffixal derivatives, e.g. przetestować, ukameralnić, urynkowić were formed in the process of transformation of syntactic compounds involving a pattern verb, which provided the prefix for the new derivative introducing it at the same time to the whole group of derivatives with a similar structural meaning.